The Effect of Fitness Training on Cardiorespiratory Fitness (VO₂max) of Elementary School Teacher Education Students: A Quasi-Experimental Study - Anung Probo Ismoko; Yudha Febrianta; Danny Ontario Rusmono; Amri Ikhsanul Amal; Dea Amanda; Dwi Kristi Fadila; Yulia Widya Ningsih (Universitas Muhammadiyah Purwokerto, 2026)
Fitness is a course that emphasizes structured physical exercise to improve students' physical fitness. Objective: To assess the effect of fitness training on cardiorespiratory fitness (VO₂max) in PGSD students at Muhammadiyah University of Purwokerto. Method: Quasi-experimental study with one group pretest–posttest design. A total of 40 students completed the program for 12 sessions (3 times/week). VO₂max was measured using the Multistage Fitness Test (MFT) before and after the intervention. Prerequisite tests included normality and homogeneity, followed by a paired t-test (α=0.05). Results: The mean VO₂max increased from 29.19 to 31.54, the mean increased to 2.34 or 8.0%, with a significant difference (t(39)=3.923; p<0.01). The distribution of fitness categories shifted towards the better. Conclusion: Fitness training is effective in improving the cardiorespiratory fitness of PGSD students.